Empowerment of UMKM Umah Labah An Nahl Farm and Education in improving Trigona honey bee cultivation - Syamsurizal, S.; Fuadiyah, Sa'diatul; Kurniawati, Tri; Badriyya, Elsa (Pelita Eksakta, 2025)
The kelulut / Trigona bee business development sector is still carried out as a small-scale business and is still far away when compared to other countries that have been able to produce large-scale honey production. Indonesia's honey production has only reached around 2,000 tons / year with a low level of honey consumption per capital, which is around 10 to 15 grams / person / year or only equivalent to one tablespoon per person per year. UMKM Umah Labah An Nahl Farm and Education located in Cimpua Pasa Durian village, Nagari Lareh Nan Panjang Sungai Sariak, Padang Pariaman Regency was founded by Febri Mulyadi, S.Pd. with two colleagues two years ago. In general, kelulut beekeepers in Cimpua village have not been organized in containers such as farmer groups or cooperatives so that they work individually so that their business progress has not been encouraging, including Umah Labah. This UMKM Umah Labah An Nahl Farm and Education is just developing and has various problems, including: 1. Marketing or marketing; 2. Educating consumers about the taste and quality of honey; 3. Working partners (retailers and so on) in adjusting prices; 4. Choosing good and attractive packaging and 5. Taking care of licensing correspondence. Thepurpose of the service is to develop superior products of Padang Pariaman Regency produced by Umah Labah An Nahl Farm and Education MSMEs to improve the quality and quantity of products / services to be highly competitive